1998
DOI: 10.1002/(sici)1096-9861(19980504)394:2<139::aid-cne1>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and localization of neurohypophysial peptides in the brain of a caecilian amphibian,Typhlonectes natans (amphibia: Gymnophiona)

Abstract: The amphibian order Gymnophiona contains more than 150 different species of caecilians. The characterization and distribution of neurohypophysial peptides, however, has not been described for any member of this order. By using high-performance liquid chromatography, radioimmunoassay, and mass spectrometry, we identified the peptide arginine vasotocin (AVT) in brain and pituitary extracts from the caecilian Typhlonectes natans. By using immunocytochemistry, we found five populations of AVT-immunoreactive (AVT-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…In addition, most species exhibit a fairly dense AVT/AVP-ir innervation of the periaqueductal midbrain (not recognized in birds) and adjacent tegmentum, ventral tegmentum (particularly the ventral tegmental area), and isthmal regions (periventricular isthmus, nucleus isthmi, locus coeruleus). Hindbrain label typically includes the lateral aspect of the medulla and a concentration of AVT/AVP -ir fibers in viscerosensory regions such as the nucleus of the solitary tract and/or the area postrema (no review is currently available, see these recent whole brain descriptions: Propper et al, 1992;Lakhdar-Ghazal et al, 1995;Lowry et al, 1997;Hilscher-Conklin et al, 1998;Panzica et al, 1999). Homologies between teleosts and tetrapods for specific AVT/AVP-innervated structures of the anterior and lateral hypothalamic regions are not firmly established, whereas the relationships between other regions containing AVT/AVP-ir fibers are more clear (POA, periaqueductal gray; Nieuwenhuys et al, 1998;Northcutt, 1981).…”
Section: Comparison With Avt Immunoreactivity In Other Vertebrate Taxamentioning
confidence: 99%
“…In addition, most species exhibit a fairly dense AVT/AVP-ir innervation of the periaqueductal midbrain (not recognized in birds) and adjacent tegmentum, ventral tegmentum (particularly the ventral tegmental area), and isthmal regions (periventricular isthmus, nucleus isthmi, locus coeruleus). Hindbrain label typically includes the lateral aspect of the medulla and a concentration of AVT/AVP -ir fibers in viscerosensory regions such as the nucleus of the solitary tract and/or the area postrema (no review is currently available, see these recent whole brain descriptions: Propper et al, 1992;Lakhdar-Ghazal et al, 1995;Lowry et al, 1997;Hilscher-Conklin et al, 1998;Panzica et al, 1999). Homologies between teleosts and tetrapods for specific AVT/AVP-innervated structures of the anterior and lateral hypothalamic regions are not firmly established, whereas the relationships between other regions containing AVT/AVP-ir fibers are more clear (POA, periaqueductal gray; Nieuwenhuys et al, 1998;Northcutt, 1981).…”
Section: Comparison With Avt Immunoreactivity In Other Vertebrate Taxamentioning
confidence: 99%
“…Moreover, the same antibodies have been applied to the brains of teleost fish (Van den Dungen et al, 1982), reptiles (Smeets et al, 1990;Stoll and Voorn, 1985;Thepen et al, 1987), and mammals (e.g., Buijs , 1978;De Vries et al, 1985). Studies of AVT and MST systems in amphibians by other researchers Hilscher-Conklin et al, 1998;Lowry et al, 1997) using different antisera have revealed comparable results. Therefore, it is now generally accepted that, in addition to a well-developed hypothalamo-hypophysial system, extrahypothalamic AVT-and MST-immunoreactive cell groups as well as extensive networks of immunoreactive fibers are present in all amphibians studied so far, thus confirming the phylogenetic constancy of this feature.…”
Section: Amphibian Avt and Mst Systemsmentioning
confidence: 99%
“…Similar work continues to be done on courtship behavior in two of the three major amphibian groups, the urodeles (salamanders and newts) and the anurans (frogs and toads). The third group, the apodans, is largely uninvestigated outside of neuroanatomical studies (Pinelli et al, 1997;Hilscher-Conklin et al, 1998;Ebersole and Boyd, 2000). The urodeles and anurans share some basic behavioral characteristics, such as males producing advertisement signals and females using them for mate choice, and the presence of amplexus or stereotyped clasping behavior in which males tightly grasp females as females and males release gametes for external fertilization.…”
Section: Introductionmentioning
confidence: 99%